The Applications of Ionic Liquid as Functional Material: A Review - Liu, Baoyou; Jin, Nanxi (Current Organic Chemistry, 2016)
As the high-profile new environmental material, ionic liquid is widely used in various fields with its extraordinary performance. It can be used as a substitute of traditional functional material and it also provides a theoretical basis for research and development of new material. This paper introduced the applications of ionic liquid in physical, chemical and biological areas as lubricant, plasticizer, variable focus lenses, optical response material, optical monitoring CO2 sensor, anti-static agent, energy storage battery, thermal material, magnetic material, intelligent material, gas absorption material, catalyst, refrigerant, antibacterial agent and herbicide, respectively. The ionic liquid materials usually provided better properties than traditional functional materials with wider application conditions and amazing effects. It is noteworthy that the ionic liquid is a green material for its environmental characteristics and economic benefits. At last, the further expectations of ionic liquid applied in material fields were put forward.
Keywords: functional material